The MicroRNA Expression Profile Differs Between Erythrodermic Mycosis Fungoides and Sézary Syndrome - Anne Hald Rittig; Lise M. Lindahl; Claus Johansen; Pamela Celis; Niels Ødum; Lars Iversen; Thomas Litman (Medical Journals Sweden, 2019)
It is difficult to distinguish erythrodermic mycosis fungoides from Sézary syndrome due to their similar clinical and histological features. The main purpose of this study was to investigate whether microRNA expression profiles in lesional skin could discriminate patients with erythrodermic mycosis fungoides from those with Sézary syndrome. A further aim was to assess whether the microRNA expression profiles in erythrodermic mycosis fungoides skin was more comparable to microRNA expression profiles of Sézary syndrome or early-stage mycosis fungoides. RNA was extracted from diagnostic skin biopsies, followed by quantitative reverse transcription polymerase chain reaction analysis of 383 microRNAs. Twenty-seven microRNAs were significantly differentially expressed between erythrodermic mycosis fungoides and Sézary syndrome. Moreover, erythrodermic mycosis fungoides showed microRNA features overlapping with Sézary syndrome and early-stage mycosis fungoides, although hierarchical cluster analysis co-clustered erythrodermic mycosis fungoides with early-stage mycosis fungoides rather than with Sézary syndrome. These findings underscore that erythrodermic mycosis fungoides and Sézary syndrome are different diseases.